Beyond Participation: A Case Study of Youth As Researchers and Community Development in North Philadelphia. Issue 5 (19th October 2020) - Malcolm, Jamison; Brennan, Mark; Webster, Nicole; Dolan, Pat
ABSTRACT: Young people (ages 15-25) are globally the largest and fastest growing segment of the population. While youth increase in number, the challenge and opportunity facing communities around the world is to create meaningful avenues for youth participation in civic, economic and academic life. This article presents a research narrative describing a youth participatory action research program implemented in North Philadelphia in 2017. Through this process, youth researchers identified a social justice topic of critical interest to them (community/police violence), collected primary qualitative data and reported their findings. The impact that participation had on the youth researchers, the local community, and local police/community interaction is described. Finally, recommendations are given for increasing the scope/impact of the program and implications for program and policy.